Pengembangan Bahan Ajar Biologi Materi Virus Berbasis SocioScientific Issues (SSI) untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Diyana Septiningrum; Nur Khasanah; Nur Khoiri (Phenomenon : Jurnal Pendidikan MIPA, 2021)
The purpose of research is to know the characteristics, feasibility and effectiveness of developing teaching materials viruses based on Socio-Scientific Issues (SSI) to improve critical thinking skills. Research method using Research and Development (RD) with a 4D step (define, design, develop, disseminate) Thiagarajan et all. The subjects of the study are 34 students class X MIPA 1 as the experimental class and 34 students class X MIPA 4 as the control class. The eligibility of teaching material is derived from the results of expert validation questionnaires, responses of biology teachers and students' responses, and effectiveness of critical thinking skills from the results of the test questions pretest and posttest. The results of the characteristics teaching material viruses based SSI include: cover, introduction, news analysis, material, summary, evaluation, bibliography and glossary. The results of the eligibility from the material expert validation questionnaire were 88,67%, 94,67% of media experts, 83,55% of teacher responses and 82,29% of students' responses. The effectiveness of teaching materials used was obtained from the difference in the average value of experimental learning outcomes of 81.84 and 76.84 kontrol class with tcount = 4.338 and ttable = 1.6682 which means tcount ttable and Ha accepted, concluded that there were differences in posttest results experimental class with kontrol class. The n-gain results obtained the value of the experimental class of 0.63 and the control class of 0.54 with their respective categories being moderate. So it can be concluded that the use of biological material teaching material based on Socio-Scientific Issues (SSI) is effective to improve students' critical thinking skills class X SMA 12 Semarang.